Cloud Point Extraction of Toxic Reactive Black 5 Dye from Water Samples Using Triton X-100 as Nonionic Surfactant - Raziyeh Mousavi; Farzin Nekouei (E-Journal of Chemistry)
A surfactant mediated cloud point extraction (CPE) procedure has been developed to remove color from wastewater containing reactive black 5, using triton x-100 (TX-100) as non-ionic surfactant. The effects of the concentration of the surfactant, pH, temperature and salt concentration on the different concentrations of dye have been studied and optimum conditions were obtained for the removal of reactive black 5 (RB 5). The concentration of RB 5 in the dilute phase was measured using UV-Vis spectrophotometer. It was found that the separation of phases was complete and the recovery of RB 5 was very effective in the presence of NaCl as an electrolyte. The results showed that up to 600 mg L-1 of RB 5 can quantitatively be removed (>97%) by cloud point extraction procedure in a single extraction using optimum conditions.